This is not about us [compact disc, unabridged] - Goodman, Allegra (Penguin Random House, 2026)
When their beloved sister passes away, Sylvia and Helen Rubinstein are unmoored. A misunderstanding about apple cake turns into a decade of stubborn silence. Busy with their own lives, their children do not want to get involved. As for their grandchildren? Impossible.